THE PROBLEM OF SEMANTIC DIFFERENCES IN TRANSLATION: A STUDY FROM AHMAD MUKHTAR UMAR'S PERSPECTIVE - Habib, Ikhwanul; Rahmadewi, Sintya; Kabalmay, Taqiyuddin; Hasan, Nur (Yayasan Haiah Nusratul Islam, Indonesia, 2025)
This study examines semantic challenges in translation with an emphasis on problems related to ʿIlm al-Dilalah (the science of meaning). The method used is qualitative descriptive with a case study design, data collected from observations, interviews, and documents in the form of books, journals, and scientific papers on translation studies and semantic theory. Mukhtar Umar's views were highlighted, emphasizing that the core of the translation problem is the difficulty of choosing the right semantic equivalent. The findings suggest that the main problem lies in translator limitations in finding accurate and contextual equivalents of meanings. The problems that occur are differences in semantic range, contextual distribution, use of majas, partial classification differences, politeness and taboo terms in conversation. This research emphasizes the importance of deep semantic mastery for translators. This approach makes a significant contribution to the theoretical and practical aspects of translation.